Protocol for Studying Extinction of Conditioned Fear in Naturally Cycling Female Rats - Maeng, Lisa Y. (J Vis Exp, 2015)
Extinction of conditioned fear has been extensively studied in male rodents. Recently, there have been an increasing number of studies indicating that neural mechanisms for certain behavioral tasks and response behaviors are different in females and males. Using females in research studies can represent a challenge because of the variation of gonadal hormones during their estrous cycle. This protocol describes well-established procedures that are useful in investigating the role of estrogen in fear extinction memory consolidation in female rats. Phase of the estrous cycle and exogenous estrogen administration prior to extinction training can influence extinction recall 24 hr later. The vaginal swabbing technique for estrous phase identification described here aids the examination and manipulation of naturally cycling gonadal hormones. The use of this basic rodent model may further delineate the mechanisms by which estrogen can modulate fear extinction memory in females.